(untitled) (Journal of NELTA, 2018)
The utilisation of technology into classroom practices basically promotes studentcentered instructions that require teachers to be professionally well trained and confident enough to use various technology tools and resources. This study was conducted to explore secondary school EFL teachers’ experiences and practices of modern technology usage into their classroom pedagogy and possible impediments of utilizing technology tools. Eight EFL teachers were purposefully selected from public secondary schools of the Kathmandu valley. A semi-structure interview was administered to collect the required data. The thematic data analysis revealed that the EFL teachers employed different pedagogical strategies for the effective integration of technology; however, some impediments were identified such as insufficient professional ICT skills and knowledge of EFL teachers, inadequate ICT infrastructure at school, teachers’ workload and time constraint, and digital device among students. This study suggests that EFL teachers need professional development trainings particularly designed on the TPACK framework, adequate ICT infrastructure at school, revised teachers’ workload and time constraint, and supportive school environment to promote technology utilization into EFL pedagogy.